PENGARUH MOTIVASI DAN KOMPETENSI TERHADAP KINERJA KARYAWAN PT. PUSAKA SINAR DIAN ABADI KABUPATEN PALI - Sudarta, Sudarta; Puspasari, Mardiana; Ardiansyah, Al Fitrah (Bussman Journal : Indonesian Journal of Business and Management, 2021)
This study aimed to determine whether there was any effects of motivation and competence on employee performance of PT. Pusaka Sinar Dian Abadi, Kabupaten PALI. This type of research used associative research. The sample in this study were 52 respondents from a total population of 110 employees. The sample data collection technique used purposive stratified technique. The collection method used a questionnaire and documentation. The data analysis in this study used quantitative qualitative data analysis. Data processing techniques used multiple linear regression analysis, F test, t test and correlation coefficient. The results of the study with the F test showed that there was a significant effect of motivation and competence on employee performance of PT. Pusaka Sinar Dian Abadi. The results of the t test showed that there was a significant effect of motivation on employee performance, there was a significant effect of competence on employee performance of PT. Pusaka Sinar Dian Abadi